Model GBHN dalam Sistem Perencanaan Pembangunan Nasional Ditinjau dari Sistem Pemerintahan Menurut UUD NRI 1945 - Septaviana, Diana; Razak, Muhamad Abdul (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The assembly of the civil servants (MPR) brought planning on enforcing the constitution (bill) of 1945, with the addition of one verse in chapter 3 that authorized the MPR to change and establish points of state (PPHN). The problem is that there are varying GBHN views. Those supporting the state's course felt that the country's course was important. The Indonesian government has a strong opinion of its leaders. Research employs a type of study of normative (normative), which isa kind of study by study and includes isa analyses under another regulatory rule and written source. Studies have shown that those who support the state's course feel that the country's course is important. A country's course is necessary for an Indonesian nation especially developing country to give power in both direction and certainty to development countries' goals. The views of those who disagree with a country's course also have their thoughts. The vice plan could give MPR a way to become the highest institution again. When GBHN or the state course is re-enforced, the MPR can seize the President at any time. There is also the thought that enacting a course of the state could actually set democracy back.